Association between SOD2 V16A variant and urological cancer risk - Zhang, Li-Feng; Xu, Kai; Tang, Bo-Wen; Zhang, Wei; Yuan, Wei; Yue, Chuang; Shi, Li; Mi, Yuan-Yuan; Zuo, Li; Zhu, Li-Jie (Aging (Albany, NY.), 2020)
The correlation between superoxide dismutase 2 (SOD2) V16A variant and urological cancer susceptibility has been widely studied, however, with divergent results. Totally, 9,910 cancer patients and 11,239 control subjects were enrolled. V16A variant is associated with an increased susceptibility to urological cancer (A-allele vs. V-allele: OR = 1.06, 95% CI = 1.00 - 1.13, = 0.047; AA+AV vs. VV: OR = 1.09, 95% CI = 1.02 - 1.16, = 0.008), especially for prostate cancer (PCa). Serum SOD2 level of PCa patients with VV+VA genotypes was lower than in those with AA genotypes. SOD2 expression is downregulated in both prostate and bladder cancer, as compared to the control. Furthermore, SOD2 was found to be downregulated in more advanced PCa participants, as compared to the ones in early stages. PCa subjects with low SOD2 expression displayed a shorter disease-free survival (DFS) time compared to that of the high SOD2 expression counterparts. The SOD2 V16A variant may be associated with increased urological cancer susceptibility, especially for prostate cancer. A pooled analysis utilizing odds ratios (ORs), tools and ELISA was adopted to demonstrate this association. We also used immunohistochemical staining (IHS) to assess SOD2 expression.